RISALAH TUNBIAT AL HAYAT: PENYAJIAN TEKS DISERTAI DENGAN DISKUSI PRELIMINER - Windayanto, Riqko Nur Ardi (Tambo: Journal of Manuscript and Oral Tradition, 2024)
This research presents an edited text edition of the Risalah Tunbiat Al Hayat and interprets it with a preliminary discussion. The diplomatic method and literature study are used in this research. This text contains the effects and earthquakes according to the time they occurred, the time and place of house construction, the fate, dragons, magical rites, as well as tables and descriptions of the humans’ fate and character based on the seven stars. Based on the content of the text, the Malay people see the natural and social phenomena around them as powers that imply the division of God’s power. However, Allah and Islam remain the central associations of this Malay text. This can be understood as the Malay people’s way of explaining life patterns, including fate and character according to astrology as Islamic astrology’s influence. Thus, this research has presented the twin tasks of philology: presenting and interpreting text.